Ichthyotoxic properties and essential oils of Syzygium malaccense (Myrtaceae) - Ismail, Intan Safinar; Ismail, Nor Akmar; Lajis, Md. Nordin (Universiti Putra Malaysia Press, 2010)
The preliminary ichthyotoxic test on all parts of Syzygium malaccense (Myrtaceae) revealed that the leaves fraction was the most ichthyotoxic against tilapia-fish (Tilapia oreochromis). Three compounds, namely ursolic acid (1), β-sitosterol (2) and sitost-4-en-3-one (3), were isolated and their structures were elucidated with the aid of spectroscopic data and comparison with previously reported investigations. However none of these compounds gave any significant ichthyotoxicity. The volatile constituents of the leaves and fruit were determined by Gas Chromatography-Mass Spectrometer (GC-MS), with 180 and 203 compounds being identified in the aroma concentrates, respectively.